2000
DOI: 10.1159/000029458
|View full text |Cite
|
Sign up to set email alerts
|

Limited Additive Value of Pleural Fluid Carcinoembryonic Antigen Level in Malignant Pleural Effusion

Abstract: Objective: To assess the additive value of pleural fluid carcinoembryonic antigen (CEA.PF) level in the diagnosis of malignant pleural effusion. Methods: Thoracentesis and closed pleural biopsy were performed in consecutive patients with pleural effusions. CEA.PF, cell analysis, and biochemical, cytopathologic and microbiologic studies were carried out. Further diagnostic interventions were undertaken if initial tests were inconclusive. Results: A total of 176 patients were evaluated. The effusions proved mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…A large number of studies on the potential diagnostic value of pleural tumor markers have been published, which report either encouraging or disappointing results (Wobbes et al, 1992;Garcia-Pachon et al, 1997;Riantawan et al, 2000;Paganuzzi et al, 2001). The disagreement in results can be attributed to different factors, including the heterogeneity of tumor types, the appropriate inclusion of paramalignant PE to calculate test performances, the sometimes underpowered series, and the use of different methodologies and cut-off values in tumor marker assays (Porcel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies on the potential diagnostic value of pleural tumor markers have been published, which report either encouraging or disappointing results (Wobbes et al, 1992;Garcia-Pachon et al, 1997;Riantawan et al, 2000;Paganuzzi et al, 2001). The disagreement in results can be attributed to different factors, including the heterogeneity of tumor types, the appropriate inclusion of paramalignant PE to calculate test performances, the sometimes underpowered series, and the use of different methodologies and cut-off values in tumor marker assays (Porcel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) is a commonly used biomarker of MPE, and it is recommended as a useful biomarker in postoperative monitoring and curative effect observation [7][8][9][10][11]. However, it is known that CEA has some limitations [7,10,12]. Therefore, there is an urgent need for the development of another clinically valuable biomarker, which can be used independently or simultaneously with CEA in MPE diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that a combination of two or more markers is more powerful than a single marker. However, the real diagnosis predictability power of these markers was not assessed in many of these studies, since the cytological presence of tumor cells was detected in the pleural effusions of the patients (911). Many of the abovementioned markers were found to be elevated in the pleural effusions of cancer patients as compared to the benign pleural effusions (7).…”
Section: Introductionmentioning
confidence: 99%
“…EMT is known to mediate the many alterations and the resultant phenotype modulation in tumor architecture. EMT is characterized by the disruption of intercellular adhesion, elevated tumor cell motility, decreased susceptibility to anoikis and apoptosis and in the release of cells from epithelial tissue (911). The released tumor cells, which are resistant to anoikis, assume mesenchymal-like phenotype that is suitable for migration, invasion and dissemination, all contributing to metastatic progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation